UJI DAYA HAMBAT EKSTRAK ETIL ASETAT PANDAN (Freycinetia sessiliflora Rizki.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - ferdinan, ade (Jurnal Komunitas Farmasi Nasional, 2023)
ABSTRAC Research has been carried out to inhibit Escherichia coli bacteria. Ethyl acetate extract of Freycinetia sessiliflora R, which is one of the pandan species found on Mount Passi, Singkawang City, West Kalimantan, using the diffusion method with concentrations of 4%, 8% and 12%. The results of this research have medium category antibacterial activity with an average inhibitory of 6.20 mm. Key words: Freycinetia sessiliflora R. Escherichia coli, antibacterial activity